Grip strength, gait speed, and trajectories of cognitive function in community‐dwelling older adults: A prospective study. Issue 1 (14th February 2023) - Wu, Zimu; Woods, Robyn L.; Chong, Trevor T.‐J.; Orchard, Suzanne G.; Shah, Raj C.; Wolfe, Rory; Storey, Elsdon; Sheets, Kerry M.; Murray, Anne M.; McNeil, John J.; Ryan, Joanne
Abstract: Introduction: This study investigated whether grip strength and gait speed predict cognitive aging trajectories and examined potential sex‐specific associations. Methods: Community‐dwelling older adults ( n  = 19, 114) were followed for up to 7 years, with regular assessment of global function, episodic memory, psychomotor speed, and executive function. Group‐based multi‐trajectory modeling identified joint cognitive trajectories. Multinomial logistic regression examined the association of grip strength and gait speed at baseline with cognitive trajectories. Results: High performers (14.3%, n  = 2298) and low performers (4.0%, n  = 642) were compared to the average performers (21.8%, n  = 3492). Grip strength and gait speed were positively associated with high performance and negatively with low performance ( P ‐values < 0.01). The association between grip strength and high performance was stronger in women (interaction P  < 0.001), while gait speed was a stronger predictor of low performance in men (interaction P  < 0.05). Discussion: Grip strength and gait speed are associated with cognitive trajectories in older age, but with sex differences. Highlights: There is inter‐individual variability in late‐life cognitive trajectories. Grip strength and gait speed predicted cognitive trajectories in older age. However, sex‐specific associations were identified. In women, grip strength strongly predicted high, compared to average, trajectory. In men, gait speed was a stronger predictor of low cognitive performance trajectory.